HUBUNGAN KUALITAS AIR MINUM DENGAN KEJADIAN DIARE PADA BALITA DI WILAYAH KERJA PUSKESMAS BANYUASIN KECAMATAN LOANO KABUPATEN PURWOREJO (The Relationship Between The Quality Of Drinking Water and The Occurrence Of Diarrhea In Children Under Five Years In - Nurul Aini; Mursid Raharjo; Budiyono Budiyono (Jurnal Kesehatan Masyarakat (Undip), 2016)
Diarrhea is defined as the passage of three or more loose or liquid stools per day (or more frequent passage than is normal for the individual). In 2014, the prevalence of diarrhea in children under five years is 12,2% out of 623 children under five years at PHC Banyuasin. The aim of this study was to prove the relationship between the quality of drinking water and the occurrence of diarrhea in children under five years at PHC Banyuasin. This research is an analytic observational with cross sectional approach. A sample of 80 out of 503 children under five years with proportional random sampling technique. Measurement type of drinking water sources and hygiene of cutlery and drinking utensil using interviews with respondents and observation. While the bacteriological quality of drinking water by MPN 5-1-1 test and IMVCM. The results of univariate analysis showed the percentage of diarrhea was 32.5%, not standard bacteriological quality was 43.8%, unprocessed drinking water sources was 78.8%, and uncleaned cutlery and drinking utensil was 91.2%. The results of bivariate analysis showed there was no relationship between the bacteriological quality of drinking water (p=0.764), the type of sources of drinking water (p=0.141), and the hygiene of cutlery and drinking utensil (p=1.000) and the occurrence of diarrhea in infants. The conclude from this study was proportion of toddler diarrhea was smaller, proportion of bacteriological quality of E. coli was smaller, proportion of unprocessed drinking water sources was greater, proportion of uncelaned cutlery and drinking utensil was greater, there was no relationship between the bacteriological quality of drinking water, the type of drinking water sources, the hygiene of cutlery and drinking utensils and the incidence of diarrhea in children under five years.